2004
DOI: 10.1021/ma048239d
|View full text |Cite
|
Sign up to set email alerts
|

A Recoverable, Metal-Free Catalyst for the Green Polymerization of ε-Caprolactone

Abstract: n-Propylsulfonic acid-functionalized porous and nonporous silica materials are evaluated in the ring-opening polymerization of -caprolactone. All catalysts allow for the controlled polymerization of the monomer, producing polymers with controlled molecular weights and narrow polydispersities. Polymerization rates are low, with site-time yields generally 1-3 orders of magnitude lower than metalbased systems. The catalysts are easily recovered from the polymerization solution after use and are shown to contain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 65 publications
(174 reference statements)
1
20
0
Order By: Relevance
“…Although some metal complexes might be grafted onto a silica or alumina support, 13,[20][21][22][23] the regeneration and recycle was unsuccessful. 20 From the perspective of green chemistry, further development of a recoverable polymer-supported catalyst is desired. As a recent synthesis of PCL, ROP of e-caprolactone catalyzed by enzyme is also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although some metal complexes might be grafted onto a silica or alumina support, 13,[20][21][22][23] the regeneration and recycle was unsuccessful. 20 From the perspective of green chemistry, further development of a recoverable polymer-supported catalyst is desired. As a recent synthesis of PCL, ROP of e-caprolactone catalyzed by enzyme is also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study, the effect of porosity and structure of porous and nonporous silica supports on the reaction rate during ring‐opening polymerization of ε‐caprolactone was reported 59. The polymerization was carried out at 52 °C with sulfonic acid immobilized on silica supports and it was demonstrated that supported catalysts were less active than the homogeneous system presumably due to internal diffusion limitations inherent in porous solid catalysts.…”
Section: Heterogeneous Catalysis: Silicate and Clay‐based Initiation mentioning
confidence: 99%
“…In this case, Cab-O-Sil M5, a nonporous silica, is used as the support to avoid potential pore clogging issues associated with polymerization with porous materials as the supports [18][19].…”
Section: Introductionmentioning
confidence: 99%